2002
DOI: 10.1002/ajh.10209
|View full text |Cite
|
Sign up to set email alerts
|

Danazol for the treatment of thrombocytopenia in patients with myelodysplastic syndrome

Abstract: Thrombocytopenia is a poor prognostic indicator in the myelodysplastic syndromes (MDS). Treatment options for patients with symptomatic thrombocytopenia are limited. Danazol, an attenuated androgen, may have some efficacy in increasing the platelet count of patients with MDS. We retrospectively reviewed 33 patients with primary MDS who were treated with danazol for 6 or more weeks. After 6 weeks on danazol, the mean platelet count increased from 42 × 10 9 /L to 60 × 10 9 /L (P < 0.015), and 25 out of 33 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…A previous study has described a better response to ATG in patients with trisomy 8 and found that trisomy 8 cells within BM were preferentially suppressed by cytotoxic T lymphocytes [36]. The unexpectedly encouraging outcome highlighted the complementary and synergistic properties between CsA and LMS, also at least partly due to the addition of danazol, which demonstrated the efficacy in MDS in the earlier literature [37,38], although this was controversial [39]. …”
Section: Discussionmentioning
confidence: 64%
“…A previous study has described a better response to ATG in patients with trisomy 8 and found that trisomy 8 cells within BM were preferentially suppressed by cytotoxic T lymphocytes [36]. The unexpectedly encouraging outcome highlighted the complementary and synergistic properties between CsA and LMS, also at least partly due to the addition of danazol, which demonstrated the efficacy in MDS in the earlier literature [37,38], although this was controversial [39]. …”
Section: Discussionmentioning
confidence: 64%
“…MDS can be associated with immune thrombocytopenic purpura (ITP) and other autoimmune disorders; these patients may respond to the combination of corticosteroids and intravenous immunoglobulin. Danazol has also been studied in MDS-associated thrombocytopenia but has not been evaluated in a large prospective trial [20]. It may be beneficial in patients who have immunemediated cell destruction.…”
Section: Thrombopoietic Growth Factorsmentioning
confidence: 97%
“…Danazol is also effective to treat thrombocytopenia during myelodysplastic syndromes (MDS) [51][52][53], which represent the major differential diagnosis of ITP, notably in the elderly. Thus, when the diagnosis is not clearly established between ITP and MDS despite bone marrow explorations, danazol could be an interesting therapy.…”
Section: Danazolmentioning
confidence: 99%